2011
DOI: 10.1039/c1an15695k
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption induced surface-stress sensing signal originating from both vertical interface effects and intermolecular lateral interactions

Abstract: This research investigates the origin of specific molecule-adsorption induced surface-stress for micro/nano-cantilever bio/chemical sensors. Systematic discussion is presented on the contribution from types of molecule interactions to the generated surface-stress sensing signal. With the main arguments verified by our micro-cantilever sensing experiments, the origin of the adsorption induced surface-stress is, for the first time, clearly categorized into interface vertical effects and lateral interactions, whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 37 publications
0
11
0
1
Order By: Relevance
“…This discrepancy between the reported results in previous studies was attributed to the dependence of surface stress generation on the grain size of Au immobilization surface. More recently, Yang et al [ 100 ] reported that the origin of surface stress is due to interface vertical effects and lateral interactions. They had carried out experiments with rectangular silicon dioxide cantilever with a thin U-shaped SCS piezoresistor, silicon dioxide insulating layer, and immobilization layer realized with thin film of Au (cantilever dimensions: L C × W C × T C = 90 × 20 × 1.0 µm 3 ).…”
Section: Theory Of Surface Stressmentioning
confidence: 99%
“…This discrepancy between the reported results in previous studies was attributed to the dependence of surface stress generation on the grain size of Au immobilization surface. More recently, Yang et al [ 100 ] reported that the origin of surface stress is due to interface vertical effects and lateral interactions. They had carried out experiments with rectangular silicon dioxide cantilever with a thin U-shaped SCS piezoresistor, silicon dioxide insulating layer, and immobilization layer realized with thin film of Au (cantilever dimensions: L C × W C × T C = 90 × 20 × 1.0 µm 3 ).…”
Section: Theory Of Surface Stressmentioning
confidence: 99%
“…This large surface stress was attributed to surface charge redistribution that led to the rearrangement of the gold surface atoms. Alkane chains or vertical interactions, 11 which are the main components of biomolecular forces, only generate surface stresses on the order of 1 mN/m. Hence, gold-coated cantilevers need to operate at the lower end of their sensitivity in the presence of large common-mode error.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The generated stress is a combination of the interfacial interaction due to adsorption on the surface and of the adjacent-molecule interaction between the different water molecules. 36 Since this phase happens before surface saturation, the adsorption kinetics is dependent on both water vapour concentration and free site availability, thus showing a very large difference in absolute deflection for a cantilever with and without an enhanced area by mesoporous silica film. After 60% RH, cantilever deflection tends to a plateau for both microcantilever sensors, because the impact of water condensation is large for mass loading (Fig.…”
Section: Resultsmentioning
confidence: 99%